How do predatory medical journals try to seduce and fool potential authors?: Analysis of an 18-months monitoring survey - van Loon Olaf R.; van Loon Tom A.J. (Scripta Medica)
Background/Aim: Predatory medical publishers have developed - and still continue to develop - 'tricks' that are intended to fool potential authors with the objective to attract manuscripts. They do so because authors have to pay them article processing charges and these are commonly their exclusive business model. Authors become ever more reluctant to publish in predatory journals because such journals are not considered as scientifically reliable and the articles in such journals are commonly not or hardly read (and even more rarely cited). Particularly young scientists can nevertheless be relatively easily seduced by the promises of predatory journals, which tend to approach potential authors in an aggressive way. This study aimed to analyse how often aggressive advertising is synonym for predatory. Methods: The 322 medical journals and their 105 publishers that approached us from 1 January 2023 to 1 July 2024 period with the request to contribute a manuscript were analysed. The analysis dealt with several aspects that may give insight into the trustworthiness of these journals and their publishers, viz the International Standard Serial Number (ISSN), the Editor-in-Chief, the publishing history, the publisher's location and the journal title. Results: Only 85 (26.3 %) of the journals under study had an Editor-in-Chief and 47 (14.6 %) of the journals had no ISSN. The great majority of the journals started after 2010; the journal titles seem aimed at raising confusion with established journals and many publishers were not housed where they pretend to be. Conclusions: Checking the above aspects of journals is an important tool helping recognise the predatory character of a journal.